A Rare Case of Immunoglobulin G4-Related Constrictive Pericarditis Diagnosed Via Multimodality Imaging - Sacide S. Ozgur MD; Ariana Tagliaferri MD; Arielle Aiken MD; Binoy Desai DO; Rachel Abboud DO; Yezin Shamoon MD; Tamer Akel MD; Monisha Singhal MD; Fayez Shamoon MD (SAGE Publishing, 2024)
Constrictive pericarditis (CP) presents as a pathophysiological state where the pericardium becomes inelastic due to fibrotic changes, most commonly secondary to a protracted inflammatory process. The disease is characterized by compromised diastolic cardiac function due to loss of pericardial compliance. Immunoglobulin G4 (IgG4)-related disease, an entity marked by the insidious proliferation of IgG4-positive plasma cells and subsequent fibrosis within various organs, is an infrequent but recognized cause of CP. A case of a 55-year-old male patient with clinical manifestations of dyspnea and edema in the lower extremities elucidates the diagnostic complexity inherent to CP. Echocardiography revealed a constellation of signs, including annulus reversus, septal bounce, and a congested inferior vena cava; cardiac magnetic resonance imaging (MRI) demonstrated diffuse pericardial thickening with delayed gadolinium enhancement, suggestive of a long-term inflammatory state; and right heart catheterization confirmed the hemodynamic hallmark of CP-equalization of diastolic pressures across the cardiac chambers. The serological analysis elicited elevated serum levels of IgG4 and IgE, pointing to the differential diagnosis of IgG4-related disease. Given the nonspecific clinical presentation of IgG4-related CP, a heightened index of suspicion combined with a systematic approach to imaging and serological evaluation is paramount.